Expression of PTEN and its pseudogene PTENP1, and promoter methylation of PTEN in non-tumourous thymus and thymic tumours. Issue 8 (24th January 2017) - Masunaga, Atsuko; Omatsu, Mutsuko; Kunimura, Toshiaki; Uematsu, Shugo; Kamio, Yoshito; Kitami, Akihiko; Miyagi, Yohei; Hiroshima, Kenzo; Suzuki, Takashi
Abstract : Aims: Mutation or promoter methylation of the phosphatase tensin homologue deleted on chromosome 10 tumour suppressor gene ( PTEN ) promotes some cancers. Moreover, PTENP1 ( PTEN pseudogene) transcript regulates PTEN expression and is thought to be associated with tumourigenesis in some cancers. Here, we investigated PTEN expression in thymic epithelium and thymic epithelial tumours. Methods: Immunohistochemical analysis of PTEN was performed on two non-tumourous thymus (NT) samples, 33 thymomas (three type A, eight type AB, 11 type B1, six type B2, and five type B3), and four thymic carcinomas (TCs). In 16 cases (two NT, three A, five B1, two B2, one B3 and three TC), analyses of mutations, promoter methylation and comparisons of PTEN mRNA and PTENP1 transcripts were undertaken using PCR-direct sequencing, methylation-specific PCR, and reverse-transcription real-time PCR after target cell collection with laser microdissection. Results: PTEN protein was not immunohistochemically detected in NT epithelium or types B1 or B2 thymoma cells, but was expressed in type A thymoma and carcinoma cells. Neither PTEN mutations nor promoter methylation were detected in any samples. Statistical analysis revealed that PTEN mRNA expression was highest in NT epithelium and lowest in type A thymoma cells. PTENP1 transcript expression did not significantly differ among NT, thymoma and TC samples. Conclusions: We speculated that NT epithelium and types B1/B2 thymoma cells have a mechanism of PTEN translation repression and/or acceleration of protein degradation, whereas type A thymoma cells exhibit transcriptional repression of PTEN mRNA and accelerated translation and/or protein accumulation.